Struggles for Regulatory Hardening: exploring Swedish Politics on Corporate Social Responsibility - Jönsson, Elin (The British journal of criminology, 2023)
In recent years, the idea of Corporate Social Responsibility (CSR) has undergone a shift towards hardening, illustrated by a wave of new mandatory and state-based regulation. This article aims to understand the dynamic behind this shift, by studying struggles for regulatory hardening in the Swedish Parliament. Drawing on a critical theory of contradictions, it proposes an understanding of CSR as a contradictory social formation, which structures the parliamentary struggles. Moreover, it suggests that although the hardening trend could amount to a crisis of the traditional understanding of CSR, politicians remain embedded in a neoliberal logic of regulation. The article ends with a call for research to continue to explore alternative roads towards minimizing corporate harm in the future.